Pengembangan Prototype Sistem Kendali Kualitas Air Tambak Udang - Ty, Avara Ghamaliel; Utomo, Pramudi (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
The purpose of this article is to describe the analysis, design and performance of prototype shrimp water quality control systems. This tool is expected to simplify and ease the work of shrimp farmers in checking water quality regularly. In its design consists of several steps, namely designing the design of tools, making mechanical systems, programming, and the final stage of testing. The main component that is used as the main control is Arduino Nano. Salinity sensor, DS18b20, and PH-4520C as components for monitoring water quality. 12V DC water pump as a stabilizer of the pH level in the water. Based on the results of testing the average error for the water temperature sensor, water pH sensor and salinity sensor are 0.74%, 2.06%, and 3.60%, respectively. The three error values are less than 10%. Based on the results of testing the pH of water, liquid pH up will be sprayed when the pH value of the water is less than 6.5. While the liquid pH down will be narrowed when the pH value of water is less than 8. The results of this performance test can work in accordance with the function and purpose.